Pilot Study of Eyesight Characteristics and Thickness of the Retinal Nerve Fiber and Ganglion Cell-inner Plexiform Layers in Adolescent Patients with Type one Diabetes Mellitus on an Insulin Pump - Raczyńska, Dorota; Bzoma, Beata; Sielachowicz, Katarzyna; Brandt, Agnieszka; Chomińska-Dorn, Dorota; Raczyńska, Krystyna; Glasner, Leopold; Dębska-Ślizień, Alicja; Myśliwiec, Małgorzata (Current Pharmaceutical Design, 2018)
Aim: Estimation of the ocular status in adolescents with diabetes mellitus type 1 (DM1) treated with continuous subcutaneous insulin infusion (CSII), assessment of the development of the diabetic retinopathy (DR) and nephropathy (DN) within 10 years. Methods: 37 patients (74 eyes) aged 16-33 years, treated with CSII were enrolled to the study. Baseline, and a 10- year follow-up evaluation included: best corrected visual acuity (BCVA), tonometry, slit lamp exam and fluorescein angiography (FLA). Additionally, spectral-domain optical coherence tomography (SD-OCT) was done in the 7th year of observation to assess the thickness of the retinal nerve fiber (RNFL) and the ganglion cellinner plexiform layers (GCL-IPL) complex thickness. Glycated haemoglobin (HbA1) and albuminuria were also analysed. Results: During the 10-year observation period DR (non-proliferative - NPDR, proliferative - PDR, diabetic macular edema - DME) was diagnosed in 3 (8%) patients. In the DR group: BCVA was significantly lower, intraocular pressure (IOP) levels and albuminuria were higher. There were no differences in HbA1 in both groups. The thinning of RNFL was observed in both groups. Macular RNFL, GCL-IPL complex thickness assessment showed a significantly higher number of borderline results in the group with DR. Conclusions: Diabetic patients treated with CSII are at a lower risk of developing vascular complications even with poor metabolic control. Increased albuminuria may be a predictive sign for early ocular complications, and requires intense observation. Diagnosis of RNFL and GCL-IPL decreased values is crucial prior to diabetic retinopathy development. SD-OCT is a non-invasive, easy-to-perform, relatively inexpensive procedure, and can be a useful tool to monitor neuropathy progression.
Keywords: ganglion cell layer